(untitled) (Journal of Universal Science Research, 2024)
Advanced experiences of pedagogy and achievements in education putting it into practice is one of the important conditions of today. Now great experiences that a teacher can use during his career base has been formed and it is getting richer day by day. In this article today, the main focus is on the student, his personality and focused on his own inner world. That is why the modern teacher the main goal is to choose methods and forms of organization of personal educational activities students who optimally correspond to the established goal of development. In recent years, the issue of using new information technologies in schools increased more and more.